Technical and economic analysis of a solar air heating system integration in a residential building wall to increase energy efficiency by solar heat gain and thermal insulation. (November 2020) - Paraschiv, Spiru; Bărbuţă-Mişu, Nicoleta; Paraschiv, Lizica Simona
Abstract: Buildings are the major energy consumers, especially when they are located in severe climatic conditions where the energy requirements for heating and cooling are very high. Implementation of renewable energy sources in buildings to reduce their energy consumption and thus the fossil fuel consumption is a priority measure to reduce energy bill costs and greenhouse gas emissions, respectively. Although the initial cost of purchasing and installing renewable energy systems remains high, the costs associated with the operation and maintenance of these systems are negligible. This study aimed to analyse the integration of renewable energy sources in the building sector, namely the solar air heating system (SAHS), to assess the techno-economic-environmental performance of this system on reducing building energy consumption, economic benefits, and greenhouse gas emissions reduction. The paper analyses the annual efficiency of the SAHS integration into the building envelope, in a temperate-continental climate, with hot summers and cold winters. Finally, the proposed SAHS system was evaluated against the natural gas boiler heating system. The results of the financial analysis showed that the simple payback period of SAHS investment will recover in a period between 14 years to 5 years when the subsidies granted by the state are between 0% and 50%. The SAHS proposed here is economically feasible for the weather conditions and the building geographical orientation analysed and system implementation is a good solution to reduce buildings' energy consumption by using renewable energy. The results show that the implementation of SAHS efficiently reduces, depending on weather conditions, the dependence on fossil fuels by reducing the thermal energy need to heat the building by a minimum of 15.53% in 2011 and a maximum of 24, 68% in 2007. Installing SAHS on the building wall, it will reduce the building heat loss through the wall, achieving a lost heat recovery at a rate ranging between 9.8% and 12.51%. Besides the economic benefits, the paper also highlights the environmental benefits of reducing CO2 emissions. Thus, the use of this system will reduce yearly CO2 emissions, depending on weather conditions, between 38 t CO2 /year (2014) and 44 t CO2 /year (2007). Graphical abstract: